INSTITUTIONAL AND TECHNOLOGICAL ASPECTS OF THE IMPACT OF A GREEN ECONOMY ON SUSTAINABLE DEVELOPMENT: PROBLEMS AND PROSPECTS FOR TRANSITION ECONOMIES - Ikramova Shaxnoza Odilovna (Ecomind Press, 2025)
This article explores the institutional and technological aspects of the green economy and their influence on sustainable development, with particular emphasis on the challenges and prospects for transitional economies such as Uzbekistan. As countries shift from carbon-intensive growth models to greener alternatives, the transformation of institutions and the integration of innovative technologies become central components of this transition. The research outlines how regulatory frameworks, market incentives, and technological readiness determine the success of green initiatives. It highlights the interplay between institutional governance and green technology adoption in fostering long-term economic resilience. By analyzing both global and local examples, the study identifies key drivers of sustainable policy implementation in economies that are still undergoing structural and economic transitions. Furthermore, it assesses the barriers to innovation and offers practical recommendations to harmonize economic, environmental, and social goals. The findings suggest that integrated institutional support and inclusive technology transfer are essential for the successful realization of green development in transitional economies. The article is particularly relevant for policymakers, educators, and students aiming to understand how systemic reform and innovation can lead to sustainable progress.
Keywords: Green economy, sustainable development, institutional transformation, green technology, transitional economies, innovation policy, climate resilience, environmental governance, economic modernization.